Earthquake Risk and Cultural Heritage Preservation: BPBD Perspectives for Libraries, Archives, and Museums in Bandung - Lutfi Khoerunnisa; Roziya Abu; Linda Setiawati; Yayu Wulandari; Angga Hadiapurwa; Dimas Saputra (AL Maktabah, 2026)
Earthquakes threaten not only human life and infrastructure but also cultural heritage and information resources preserved in libraries, archives, and museums. One of the active fault systems in West Java, the Lembang Fault, poses significant seismic risks to Bandung and surrounding areas. This study aims to explore BPBD’s perspective on earthquake risks associated with the Lembang Fault and examine their implications for cultural heritage and information preservation in Bandung. Employing a qualitative case study approach, data were collected through semi-structured interviews with three purposively selected BPBD informants involved in disaster mitigation and preparedness activities. Data were analyzed using the Miles and Huberman interactive model, including data reduction, display, and conclusion drawing. The findings indicate that BPBD views disaster mitigation as a continuous and preventive effort involving hazard mapping, public education, institutional collaboration, emergency planning, and preparedness strategies. The study also highlights the importance of integrating disaster preparedness into preservation management to protect cultural heritage and ensure the sustainability of information resources in disaster-prone areas. This research contributes to the growing discussion on disaster preparedness within Library and Information Science, particularly in the context of cultural heritage preservation.Keywords: BPDB, Cultural heritage preservation, Disaster mitigation, Lembang Fault, , Libraries and archives preparedness